High interindividual variability in the CD4/CD8 T cell ratio and natalizumab concentration levels in the cerebrospinal fluid of patients with multiple sclerosis. (27th April 2015) - Harrer, A.; Pilz, G.; Wipfler, P.; Oppermann, K.; Sellner, J.; Hitzl, W.; Haschke‐Becher, E.; Afazel, S.; Rispens, T.; van der Kleij, D.; Trinka, E.; Kraus, J.
Summary Strongly decreased leucocyte counts and a reduced CD4/CD8 T cell ratio in the cerebrospinal fluid (CSF) of natalizumab (NZB)‐treated multiple sclerosis (MS) patients may have implications on central nervous (CNS) immune surveillance. With regard to NZB‐associated progressive multi‐focal leucoencephalopathy, we aimed at delineating a relationship between free NZB, cell‐bound NZB, adhesion molecule (AM) expression and the treatment‐associated shift in the CSF T cell ratio. Peripheral blood (PB) and CSF T cells from 15 NZB‐treated MS patients, and CSF T cells from 10 patients with non‐inflammatory neurological diseases and five newly diagnosed MS patients were studied. Intercellular adhesion molecule‐1 (ICAM‐1), leucocyte function antigen‐1 (LFA‐1), very late activation antigen‐4 (VLA‐4), NZB saturation levels, and T cell ratios were analysed by flow cytometry. NZB concentrations were measured by enzyme‐linked immunosorbent assay (ELISA). Lower NZB saturation levels (P < 0·02) and a higher surface expression of ICAM‐1 and LFA‐1 (P < 0·001) were observed on CSF CD8 T cells. CSF T cell ratios (0·3–2·1) and NZB concentrations (0·01–0·42 µg/ml) showed a pronounced interindividual variance. A correlation between free NZB, cell‐bound NZB or AM expression levels and the CSF T cell ratio was not found. Extremely low NZB concentrations and a normalized CSF T cell ratio were observed in one case. The differential NZB saturation and AM expression of CSF CD8 T cells may contribute to their relative enrichment in the CSF. The reduced CSF T cell ratio appeared sensitive to steady‐state NZB levels, as normalization occurred quickly. The latter may be important concerning a fast reconstitution of CNS immune surveillance.